New knowledge on the origin of domestication genes in goats - CGIAR Research Program on Livestock (2020)
Journal article on the origin of domestication genes in goats. One introgressed genomic region with a strong signature of selection harbors the MUC6 gene. Further experiments reveal that the nearly fixed allele of MUC6 confers an enhanced immune resistance to gastrointestinal pathogens, suggesting its advantage in modern goat breeding.